Influence of Wheatgrass Juice on Techno-Functional Properties and Bioactive Characteristics of Pasta - Keshavdeep Bawa; Arashdeep Singh; Jaswinder Kaur Brar; Vijay Kumar Reddy Surasani; Ravi Pandiselvam (Journal of Food Quality)
Pasta is an excellent source for fortification of ingredients and wheatgrass juice (WGJ) as a natural source of vital nutrients and antioxidants; the study was taken to develop WGJ-rich functional pasta. Wheatgrass juice (WGJ) was added at the rate of 33, 66, and 100% by replacing water during the mixing process of pasta. The samples were assessed by cooking quality, proximate composition, antioxidant properties, color, texture attributes, and sensory evaluation. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were performed. Incorporation of WGJ significantly (p<0.05) decreased the optimum cooking time of pasta, whereas water absorption capacity was increased. Cooking loss in pasta increased from 2.89 to 3.21% with increasing levels of WGJ from 33 to 100%. The addition of wheatgrass juice to pasta improved the nutritional and antioxidant profile significantly (p<0.05), as evidenced by increases in protein, phenolics, flavonoids, chlorophyll, and antioxidant activities (FRAP, DPPH, and ABTS). The incorporation of wheatgrass juice reduced the L value, whereas a∗ of the pasta enhanced gradually. With the addition of WGJ, the stiffness and hardness of the pasta changed dramatically. FTIR spectra validated the existence of bioactive compounds and chlorophyll pigments in pasta. Sensory data revealed that pasta containing 100% of WGJ was acceptable with the highest overall acceptability score of 7.72.